How do students respond to the use of the Sevima Edlink Application in learning at the university? - Sahlan Sahlan; Pujianti B. Donuata; Nurul Fitriani (Universitas Ahmad Dahlan, 2022)
This study aims to analyze student responses to online learning using the Sevima edlink application. The research includes a type of descriptive research with a quantitative approach. The research will be carried out in the 2021/2022 academic year. The study population was IKIP Muhammadiyah Maumere students, and the sample was 3rd and 5th-semester Physics Education Students, totaling 20 people. Sampling using a simple random sampling technique. Data was collected using a questionnaire specified in the Google Form form. Questionnaires were distributed to physics education students who took thermodynamics online courses in semesters 3 and 5. Data analysis using percentage technique. The results showed that 80.81% of students responded positively to using the Sevima Edlink application in thermodynamics lectures. From the analysis results, it can be concluded that the average student responds positively to taking online lectures on thermodynamics courses using the Sevima edlink application.